2021
DOI: 10.1002/adfm.202100850
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Oxygenation of Tissues Orchestrates Full‐Thickness Vascularization of Living Implants

Abstract: Bioengineering of tissues and organs has the potential to generate functional replacement organs. However, achieving the full-thickness vascularization that is required for long-term survival of living implants has remained a grand challenge, especially for clinically sized implants. During the pre-vascular phase, implanted engineered tissues are forced to metabolically rely on the diffusion of nutrients from adjacent host-tissue, which for larger living implants results in anoxia, cell death, and ultimately i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…Interestingly, the addition of CPO increased the swelling properties of the hydrogel, which indicated that the hydrophilic nature of CPO played a significant role in the absorption and retention of aqueous solutions. [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, the addition of CPO increased the swelling properties of the hydrogel, which indicated that the hydrophilic nature of CPO played a significant role in the absorption and retention of aqueous solutions. [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
“…Despite the longer exposure to UV‐light for the CPO‐laden hydrogels, it is likely that the hydrogels are crosslinked to a lesser degree, and thus degrade at a faster rate. [ 46 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations